Evaluating the Efficacy of Virtual Reality Exposure Therapy in Treating Social Anxiety Disorder with functional neuroimaging insights - Mahrukh Ansar, Junaid Rasool, Muhammad Imran Khan, Sadia Imran Cheema, Qurrat-ul-ain Fatima, Syed Ahmed Mahmud (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This randomized controlled trial examined the clinical efficacy of virtual reality exposure therapy(VRET) in treating social anxiety disorder (SAD) and investigated associated neural changes usingfunctional magnetic resonance imaging (fMRI). One hundred participants diagnosed withmoderate to severe SAD were randomized to receive either VRET or traditional cognitive behavioral exposure therapy over eight weeks. Symptom